Elastic-Plastic Fracture 1979
DOI: 10.1520/stp35828s
|View full text |Cite
|
Sign up to set email alerts
|

Elastic-Plastic Fracture Mechanics for Two-Dimensional Stable Crack Growth and Instability Problems

Abstract: An elastic-plastic fracture mechanics methodology for treating two-dimensional stable crack growth and instability problems is described. The paper draws on “generation-phase” analyses in which the experimentally observed applied-load (or displacement) stable crack growth behavior is reproduced in a finite-element model. In these calculations a number of candidate stable crack growth parameters are calculated for the material tested. The quality of the predictions that can be made with these parameters is test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 13 publications
2
37
0
1
Order By: Relevance
“…(5) From these results it follows that the resistance to stable crack extension of the material investigated is characterized by two distinct regions with significantly different CTOAbehavior. Following initiation of crack extension, CTOA opt decreases strongly until it reaches steady state conditions characterized by a constant value, thus confirming the earlier findings mentioned in the introduction [3]. This crack propagation phase is terminated by ∆a maxCTOA.…”
Section: Large Crack Extensionsupporting
confidence: 88%
See 1 more Smart Citation
“…(5) From these results it follows that the resistance to stable crack extension of the material investigated is characterized by two distinct regions with significantly different CTOAbehavior. Following initiation of crack extension, CTOA opt decreases strongly until it reaches steady state conditions characterized by a constant value, thus confirming the earlier findings mentioned in the introduction [3]. This crack propagation phase is terminated by ∆a maxCTOA.…”
Section: Large Crack Extensionsupporting
confidence: 88%
“…It was shown by experimental work and finite element analyses [3] that after a short initiation phase the crack tip opening angle attains a steady state condition which means that cracks propagate with a nearly constant opening angle over a wide range of crack extension. This has stimulated the hope that CTOA can be used for an efficient characterization of large amounts of ductile crack extension in large structures.…”
Section: Introductionmentioning
confidence: 99%
“…The CTOA fracture mechanics method was developed primarily to characterize the stable crack extension behavior for thin-walled materials in low constraint conditions. The early experimental work and FEA results of Kanninen et al [219] showed that after a short initiation phase the CTOA attains a steady state condition which means that the crack propagates with a nearly constant operation angle over a wide range of crack extension. Most applications of the CTOA criterion are made for thin-walled or sheet metals as used in aircraft engineering and pipeline industry.…”
Section: Ctoa Testing and Astm E2472 Developmentmentioning
confidence: 99%
“…[1][2][3][4][5][6]. These studies were conducted to develop efficient techniques to simulate crack extension and to study various local and global fracture criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the critical cracktip-opening angle (CTOA, y,) or displacement (CTOD) at a specified distance from the crack tip was shown to be the most suited for modeling stable crack growth and instability during the fracture process (e.g., Refs. [3][4][5][6][7][8]. However, some discrepancies among the various analyses have been observed at initiation of stable crack * Senior Scientist, Mechanics and Durability Branch t National Research Council Associate, Mechanics and Durability Branch growth.…”
Section: Introductionmentioning
confidence: 99%